Armed conflict injuries to the extremities a treatment manual - Lerner, A.; Soudry, M. (Springer, 2011)
Based on treatment of victims of terror attacks at a large level 1 trauma center, this book offers a staged treatment protocol ranging from primary damage control to definitive functional limb reconstruction using internal and external fixation methods.